Association between scanning frequency of flash glucose monitoring and continuous glucose monitoring‐derived glycemic makers in children and adolescents with type 1 diabetes - Suzuki, Junichi; Urakami, Tatsuhiko; Yoshida, Kei; Kuwabara, Remi; Mine, Yusuke; Aoki, Masako; Morioka, Ichiro (Pediatrics international, 2021)
Background We assessed the association between scanning frequency of flash glucose monitoring (FGM) and continuous glucose monitoring (CGM)‐derived glycemic markers in children and adolescents with type 1 diabetes. Methods Subjects consisted of 85 children and adolescents with type 1 diabetes using FGM. We assessed the association between scanning frequencies of FGM‐ and CGM‐derived metrics: Time in range (TIR) (70‐180 mg/dL), time below range (TBR) (<70 mg/dL), time above range (>180 mg/dL), and other glycemic markers – laboratory‐measured HbA1c and CGM‐estimated glucose and HbA1c (eA1c) levels in the subjects. Results The mean number of scans was 11.5 ± 3.5 (5–20) times per day, and scanning was most frequently conducted during a period of 18–24 h. Scanning frequency showed significant positive correlation with TIR (r = 0.719, P < 0.0001) and inverse correlation with time above range (r = −0.743, P < 0.0001), but did not correlate with TBR. There were also significant inverse correlations between scanning frequency and glucose, HbA1c, and eA1c levels (r = −0.765, −0.815, and −0.793, respectively, P < 0.0001). Conclusions Frequent glucose testing with FGM decreased hyperglycemia with increased TIR, but did not reduce TBR. Coping with a rapid fall of glucose and unexpected hypoglycemia with more advanced technology might contribute to a reduction in TBR.